Experimental study on pollutant emission characteristics of diesel urea-based selective catalytic reduction system based on corrugated substrate. (15th March 2023) - Zhao, Qiaonan; Yang, Qiguo; Xu, Hongtao; Jiao, Anyao; Pan, Donghui
Abstract: In this study, a corrugated substrate of diesel engines for urea-based selective catalytic reduction (urea-SCR) with V2 O5 -WO3 /TiO2 (V-SCR) and Cu-based (Cu-SCR) catalysts is proposed and the effects of the ammonia-to-nitrogen ratio α on the NO x emission, NH3 slip, and N2 O emission were experimentally investigated on a diesel engine test bench with the World Harmonized Transient Cycle (WHTC). The volume ratio of the catalyst to the engine capacity is 1.6. With the increase of α, the NO x reduction reaction of V-SCR performed better NO x emission characteristics than that of Cu-SCR. When α increased from 1.0 to 1.2, the NO x emission of V-SCR and Cu-SCR decreased from 0.44 to 0.26 g/kW·h and from 0.63 to 0.36 g/kW·h, respectively. However, the NH3 slip of Cu-SCR was less because of its absorption capacity of NH3 . The NO x conversion efficiency β and N2 selectivity δ of V-SCR outperformed those of Cu-SCR. At α = 1.1, β and δ of V-SCR were 1.07% and 3.25% higher than those of Cu-SCR, respectively. The dynamic response of V-SCR to NH3 showed high competitiveness compared to Cu-SCR. It was concluded that, based on the corrugated substrate, the V-SCR showed better pollutant emission characteristics than did the Cu-SCR. Highlights: A corrugated substrate of SCR system for diesel engines was proposed. Pollutant emission characteristics of V-SCR and Cu-SCR were compared. The pollution emission characteristics of V-SCR outperformed Cu-SCR. The NH3 slip of Cu-SCR was less than that of V-SCR based on corrugated substrate.